2007
DOI: 10.4103/1817-1737.30355
|View full text |Cite
|
Sign up to set email alerts
|

Can clinical factors be determinants of bone metastases in non-small cell lung cancer ?

Abstract: OBJECTIVE:The aim of this study was to investigate the correlations among symptoms, laboratory findings of bone metastasis and whole body bone scanning (WBBS) and the frequency of occurrence of bone metastasesMATERIALS AND METHODS:Hundred and six patients who were diagnosed with non-small cell lung cancer (NSCLC) between June 2001 and September 2005 were investigated retrospectively. Bone pain, detection of bone tenderness on physical examination, hypercalcemia and increased serum alkaline phosphatase were acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Shinto, et al (2009) found skeletal metastases in 13 patients (14.13%) out of 92 asymptomatic lung cancer patients; percentage was lower than the current study (11). Ursavas, et al (2007) reported bone metastases in 21(52.5%) of 40 symptomatic non-small cell lung cancer patients and 12(18.18%) of 66 asymptomatic patients (12). Similarly Erturan, et al (2005) noticed bone metastases in 21(53%) of 39 symptomatic non-small cell lung cancer patients, 5 (5.8%) of 86 asymptomatic patients (13).…”
Section: Discussionmentioning
confidence: 94%
“…Shinto, et al (2009) found skeletal metastases in 13 patients (14.13%) out of 92 asymptomatic lung cancer patients; percentage was lower than the current study (11). Ursavas, et al (2007) reported bone metastases in 21(52.5%) of 40 symptomatic non-small cell lung cancer patients and 12(18.18%) of 66 asymptomatic patients (12). Similarly Erturan, et al (2005) noticed bone metastases in 21(53%) of 39 symptomatic non-small cell lung cancer patients, 5 (5.8%) of 86 asymptomatic patients (13).…”
Section: Discussionmentioning
confidence: 94%
“…In recent years, the number of patients with bone metastases has increased due to the increase in the number of cancer patients and their prolonged prognoses due to advances in cancer treatment ( 1 , 2 ). Bone metastases are often asymptomatic in the early stages ( 3 ), but as they progress, they cause pain, spinal cord compression, and pathological fractures resulting in dyskinesias, paralysis, and a significantly decreased quality of life (QOL) ( 4 - 8 ). Pain is the most frequent symptom of bone metastasis.…”
Section: Introductionmentioning
confidence: 99%